2020
DOI: 10.1091/mbc.e19-11-0657
|View full text |Cite
|
Sign up to set email alerts
|

Scribble, Lgl1, and myosin II form a complex in vivo to promote directed cell migration

Abstract: Scribble (Scrib) and Lgl1 are conserved polarity proteins that play important roles in different forms of cell polarity. The roles of Scrib and Lgl1 in apical-basal cell polarity has been studied extensively, but little is known about their roles in the cell polarity of migrating cells. Furthermore, the effect of Scrib and Lgl1 interaction on cell polarity is largely unknown. In this study, we show that Scrib, through its LRR domain, forms a complex in vivo with Lgl1. Scrib also forms a complex with myosin II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 77 publications
7
19
0
Order By: Relevance
“…Interestingly, a recent study supports our conclusion that Lgl1 loss leads to migration failure as a result of Integrin β1 upregulation. Specifically, Abedrabbo and Ravid (2020) showed that reduction of Lgl1 function by short hairpin RNA knockdown in human breast cancer MDA-MB-231 cells severely reduced collective migration due to defective focal adhesions in mutant cells using the in vitro two-dimensional wound-healing assay.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study supports our conclusion that Lgl1 loss leads to migration failure as a result of Integrin β1 upregulation. Specifically, Abedrabbo and Ravid (2020) showed that reduction of Lgl1 function by short hairpin RNA knockdown in human breast cancer MDA-MB-231 cells severely reduced collective migration due to defective focal adhesions in mutant cells using the in vitro two-dimensional wound-healing assay.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, loss of Scrib frees up Lethal giant larvae (Lgl), a polarity protein in the basal Scrib-Discs large (Dlg)-Lgl complex, to bind to aPKC and Par6 creating competition between Lgl and Par3 and subsequently inhibiting the formation of tight junctions (Yamanaka et al, 2003). In the neural plate, the Scrib rumz mutation may disrupt interaction of Lgl with the Scrib LRR domain (Abedrabbo and Ravid, 2020; Kallay et al, 2006) allowing Lgl to localize to the apical membrane and bind to aPKC and Par6. The formation of an Lgl-aPKC-Par6 complex would displace Par3 from the complex and destabilize tight junctions leading to loss of ZO-1 and Par3 expression, which is what we observe in Scrib rumz/rumz mutants.…”
Section: Discussionmentioning
confidence: 99%
“…MIIA and MIIB are known to have different kinetic profiles (Kovács et al, 2003), and thus the change from MIIB to MIIA might alter cell intercalation behavior while preserving cell-cell adhesion. Alternatively, recent studies in human breast cancer cell lines demonstrated that MIIA co-immunoprecipitated with Lgl but not Scrib, and MIIB complexed with Scrib but not Lgl, demonstrating MIIA and MIIB form distinct complexes with Lgl and Scrib respectively (Abedrabbo and Ravid, 2020). Thus, the increase in MIIA we observe in the neural plate of Scrib rumz mutants may be linked to increased Lgl at the apical membrane, whereas the decreased expression of MIIB may be directly due to lack of Scrib localization to cell junctions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the cellular localizations of Lgl1 and Scrib in migrating cells is interdependent 14 . To test whether the junctional localizations of Lgl1 and Scrib is also interdependent, we stained Scrib and Lgl1 in Lgl1 KD and Scrib KD cell lines, respectively.…”
Section: Scrib Kd Cells Quantification Of E-cadherin Fluorescence Int...mentioning
confidence: 99%
“…PCR fragments were digested with BamHI and ligated into pLenti-Neon plasmid digested with BamHI. pLKO-Tet-shscrib, pLKO-Tet-shLgl1 and pLenti-Neon-Lgl1-WT were previously described 14 . To create the inducible GFP-Scrib expression vector (pVPR-GFP-Scrib), pGFP-Scrib and PB-TRE-dCas9-VPR (Addgene plasmid # 63800) 44 were digested with BamHI and PmeI, respectively, followed by fill-in reaction using Klenow fragments and digestion with BmtI.…”
Section: Preparation Of Plasmidsmentioning
confidence: 99%